Drama as a tool to improve speaking skill among students of 6th year of basic education, at “18 de Noviembre” school of loja city, during the academic year 2014-2015 - Flores Suarez, Liliana Kaherine (2016)
The present research work was developed with the purpose of improving speaking skills of students of sixth year of Basic Education through the application of drama. To develop this research some methods were used, such as the scientific, descriptive, analytic-synthetic and statistic that allowed to analyze and interpret the results. Moreover some instruments were used like tests and questionnaires that were applied to thirty students. The results showed that students improved their speaking skills considerably in four aspects: comprehension, pronunciation, fluency and accuracy. As a main conclusion the application of drama had a positive impact on students, since overcame the fear of speaking in English and their participation was more frequent and interactive.